2022
DOI: 10.1002/app.53488
|View full text |Cite
|
Sign up to set email alerts
|

Overmolded hybrid thermoset‐thermoplastic structures: Experimental study on the bonding strength of co‐curing thermoplastic film onto thermoset composite

Abstract: In the present study, an innovative approach to produce hybrid thermosetthermoplastic structure by means of co-curing technique together with injection overmolding technique is proposed. To make thermoset composite bondable, a thermoplastic film was firstly co-cured on the surface of thermoset composite. Five different types of thermoplastic film were chosen to co-cure with thermoset composite. The bonding strength between thermoplastic film

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In our previous research, we conducted lap shear tests on TSC-PA 6 structures under different process parameters and the results are shown in Figure 7. 37 It can be observed that the healing degree exhibits a similar trend to the interface bonding strength. To quantify this trend, the Pearson correlation coefficient (referred to as the correlation coefficient) is utilized to measure the degree of correlation between two variables, X and Y.…”
Section: Simulation Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…In our previous research, we conducted lap shear tests on TSC-PA 6 structures under different process parameters and the results are shown in Figure 7. 37 It can be observed that the healing degree exhibits a similar trend to the interface bonding strength. To quantify this trend, the Pearson correlation coefficient (referred to as the correlation coefficient) is utilized to measure the degree of correlation between two variables, X and Y.…”
Section: Simulation Resultsmentioning
confidence: 81%
“…The lap shear strength of TSC-PA 6 structure. 37 T A B L E 3 Orthogonal experimental results of healing degree under different process parameters.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this concern, microwave absorption [150], electrostatic shielding [151], electronics [152], engines [153], and high-end nanocomposites have been designed [154]. In addition to mechanical features [155], low weight [156], sturdiness [157], adhesion [158], and heat resilient properties of nanocarbon nanocomposites [159] have been desirable for commercial scale aerospace applications. Here, nanocarbon dispersion, associations with matrices, and interface formation have been identified as major factors enhancing the aerospace structural characteristics [160].…”
Section: Prospects and Conclusion On Polymer/carbonaceous Nanocomposi...mentioning
confidence: 99%